Letter to the editor: Use of face masks and heart rate in adults aged 18 to 60 years - Gómez Gonzales, Walter Edgar (2022)
The article published, "Use of face masks and heart rate in adults aged 18 to 60 years", in the Peruvian Journal of Health Sciences of December 22, 2022; refers to a very important daily practice that still persists in us and is the use of face masks, linked to a very important public health problem such as COVID-19. The findings of the study show significant statistical differences by type of face mask, with the KN95 being the most used face mask and the one with the greatest influence on the cardiac pulse; therefore, the team of researchers of the aforementioned article should be warmly congratulated.